A guide to business mathematics - O'Regan, Gerard (Boca Raton, FL : CRC Press, 2023)
"The success of business today is dependent on the knowledge and expertise of its employees. The need for mathematics arises naturally in business such as in the work of the actuary in an insurance company; the financial mathematics required in the day-to-day work of the banker; and the need to analyse data to extract useful information to enable the business to make the right decisions to be successful. A Guide to Business Mathematics provides a valuable self-study guide to business practitioners, business students and the general reader to enable them to gain an appropriate insight into the mathematics used in business. This book offers an accessible introduction to essential mathematics for the business field. A wide selection of topics is discussed with the mathematical material presented in a reader-friendly way. The business context motivates the presentation. The author uses modelling and applications to motivate the material, demonstrating how mathematics is used in the financial sector. In addition to the role of the actuary and the banker, the book covers operations research including game theory, trade discounts, and the fundamentals of statistics and probability. The book is also a guide to using metrics to manage and measure performance, and business economics. Foundations on algebra, number theory, sequences and series, matrix theory, and calculus are included as is a complete chapter on using software. Features: Discusses simple interest and its application to promissory notes/treasury bills. Discusses compound interest with applications to present and future values. Introduces the banking field including loans, annuities, and the spot/forward FX market. Discusses trade discounts and markups/markdowns Introduces the insurance field and the role of the actuary Introduces the fields of data analytics and operations research Discusses business metrics and problem solving Introduces matrices and their applications Discusses calculus and its applications Discusses basic financial statements such as balance sheet, profit and loss and cash account. Reviews a selection of software to support business mathematics This broad-ranging text gives the reader a flavour of the applications of mathematics to the business field and stimulates further study in the subject. As such, it will be of great benefit to business students, while also capturing the interest of the more casual reader"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business mathematics